Perancangan Video Motion Graphic Tentang Pengenalan Hewan Laut sebagai Media Edukasi untuk Usia 5-7 Tahun - Nisa, Dwi Zuhrotun; Wulandari, Sri; Ayuswantana, Alfian Candra (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2023)
Indonesia is the biggest archipelago country in the world. However, the sea in Indonesia is now increasingly polluted, so many marine animals die and become extinct even before they are identified. Therefore, there is a need for educational media about marine animals, especially for children aged 5-7 years so that they can still get to know marine animals even though they will become extinct one day. In addition, by teaching them about sea animals, they can also fall in love with sea animals and protect them. The educational media used is video motion graphics because children aged 5-7 years are at the stage of cognitive development, namely children aged 5-7 years tend to represent material through schemes, pictures and symbols. This motion graphic video is designed using the main character, a sea superhero and supporting characters in the form of talking sea animals. Apart from that, in this motion graphic video there is also a game so that it gets an interesting impression.